Development Strategy of Community-Based Tourism in Trate Village, Bojonegoro - Mohammad Mahyairudin; Luchman Hakim; Anthon Efani (Jurnal Penelitian Pendidikan IPA, 2024)
Bojonegoro is one of the districts within the administrative area of East Java province. So far, the quite large tourism potential in Trate Village has not been optimally utilized to develop it as a tourist village considering that several obstacles are still found, including weak human resources related to the entrepreneurial spirit, weak understanding of the concept of tourist villages, and so on. This research uses a qualitative approach method with descriptive explanation where the research emphasizes knowing certain phenomena. What is studied in this research is to develop a strategy for developing a community-based Trate tourist village to utilize and optimize the potential of the Trate Tourism Village and to analyze the internal and external factors that influence the development of the Trate tourist village. The results of this research are that the researcher provides the results of the Internal Strategy Factor Analysis (IFAS) in the Trate Tourism Village, obtained with a score on the strength factors of 2.15 and a score on the weakness factors of 1.10 with a total score of 3.25. The results of the analysis of External Strategy Factors (EFAS) in Trate Tourism Village were obtained with a score on the Opportunity Factor of 2.10 and a score on the Threat Factor of 1.25 with a total score of 3.35. The results of the researcher's analysis of processing data on internal factors and external factors in Trate Tourism Village obtained a score for each factor as follows: Score for strength factors = 2.15, Score for weakness factors = 1.10, Score for opportunity factors = 2.10, Score for threat factor = 1.25. The development strategy that must be implemented by the Trate Tourism Village uses the Strength Opportunities (SO) strategy and is applied based on existing strengths by exploiting opportunities in the Trate Tourism Village and taking advantage of opportunities outside the Trate Tourism Village.